2022
DOI: 10.1002/cpt.2767
|View full text |Cite
|
Sign up to set email alerts
|

Signal and Noise: Proton Pump Inhibitors and the Risk of Dementia?

Abstract: The association between proton pump inhibitor (PPI) use and dementia remains controversial. This cohort study re-examines this issue, addressing shortcomings identified in previous publications using a population-based and a high-dimension propensity-score matched cohort to follow patients for up to 22 years. Cox regression models using baseline characteristics, a lag period, and time-varying variables were used to examine the risk of dementia by cumulative PPI exposure. High-dose PPI users (> 180 days of use)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
(90 reference statements)
1
3
0
Order By: Relevance
“…Our results are similar to those published recently by Friesen et al, who suggested PPI use as a marker for poor health status 19 . We similarly assumed that the effect of PPIs was cumulative and nonreversible, as dementia is a neurodegenerative condition.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are similar to those published recently by Friesen et al, who suggested PPI use as a marker for poor health status 19 . We similarly assumed that the effect of PPIs was cumulative and nonreversible, as dementia is a neurodegenerative condition.…”
Section: Discussionsupporting
confidence: 93%
“…based on registers from one Canadian province followed three cohorts with different age groups at study start and found highest risk estimates for dementia with PPI use in the youngest cohort (start age 46 to 55 years). 24 Although the authors did not stratify by age at dementia diagnosis, this aligns with our study results displaying higher dementia rates occurring at a younger age. Overall, Friesen et al.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies investigating the association between PPIs and risk of dementia reported conflicting findings with some studies reporting a positive association, 18 , 19 , 20 , 21 while other studies showed a negative or neutral association. 22 , 23 , 24 This could possibly be owing to the heterogeneity between data availability and study design. 25 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations